Estresse e coping em vítimas de acidente de trânsito - Alves, Ludmila Minarini (2017)
The traffic-accidents (TA) are potentially stressing events, because break into the people lives and carry with them the emergency and unpredictability character. The hospitalization, that many times succeeds the accident occurrence, may contribute to increase the stress answer. Stressing situations demands from victims the mobilization of strategies to face the situation. The coping comprehend the set of cognitive and behavioral strategies end used to handle stressing situations. Thus, the present study objected to verify the relation between stress and coping in TA’s victims interned in a university hospital. The sample was composed by 10 patients who were TA’s victims. To rate the coping was applied the Coping Strategies Inventory by Folkman and Lazarus and to value the stress presence was used the Stress Symptoms Inventory for Adults by Lipp. The most of participants (80%) presented a relevant stress level, being 50% in the resistance phase, 10% in almost exhaustion phase and 20% in exhaustion phase. Between the TA’s victims who presented significant stress levels, predominated the positive reevaluation strategies, confront and issues resolution. Between the TA’s victims that didn’t present stress predominated the self-control strategies, responsibility acceptation and issues resolution. The escape/avoidance coping type had presented a positive correlation with stress level in the patients group that presented stress (p=0,835). The escape/avoidance strategy is related to worse outcome in mental health. Keeping yourself away, even cognitively, from the situation is disadvantage in the look for support. Moreover, the avoidance of stressing stimulus prevents the subject of familiarizing to the content and consequences of this situation. Although the small sample, there are some coping types that seems to collaborate for the stress answer to be smaller or bigger. Considering the psychic and physical losses of the prolonged stress, it is suggested to the health teams that work with TA’s victims to be attentive to the possibility of stress manifestations and consider this before acting up to the patients that show this impairment, encouraging a best functional confrontation of the situation.